Synergism between palm oil fuel ash and slag: Production of environmental-friendly alkali activated mortars with enhanced properties. (10th May 2018) - Huseien, Ghasan Fahim; Ismail, Mohammad; Tahir, Mahmood Md.; Mirza, Jahangir; Khalid, Nur Hafizah A.; Asaad, Mohammad Ali; Husein, Ahmed Abdulameer; Sarbini, Noor Nabilah
Graphical abstract: Highlights: Developped sustainable and high performance environmental-friendly alkali activated mortars. The inclusion of high volume POFA enhanced the setting time of alkali activated mortars. The addition of POFA improved the resistance to acid attack of alkali activated mortars. Abstract: Environmental concern raised by the production of ordinary Portland cement (OPC), is behind the search for greener construction materials and remediation. One such material is alkali activated mortars (AAMs). It is well known that the high molarity of sodium hydroxide (12–16 M) and high content of sodium silicate (sodium silicate to sodium hydroxide higher than 2.5) have negative impacts on the environment. Driven by this idea, we prepared some binary alkali activated mortars by combining palm oil fuel ash (POFA) and ground blast furnace slag (GBFS) at varying ratios. The effect of low concentration alkaline solution on the fresh, mechanical and durable properties of alkali activated was determined. The ratio of sodium hydroxide (molarity 4 M) (NH) to sodium silicate (NS) in the mixture was kept at 0.75. Microstructures of the prepared alkali activated mortars were analyzed using SEM, XRD and FTIR measurements. The achieved high strength (≈72 MPa at age of 28 days) of the alkali activated mortars was attributed to the synergy between GBFS and POFA. Partial replacement of GBFS with POFA was demonstrated to be beneficial for improving the compressive strength, durability and resistance against sulphuric acid attack. Meanwhile, calcium aluminium silicate hydrate (CASH) gel was discerned to be the main reaction product of POFA and GBFS in these binary systems. It was established that the proposed AAMs can contribute towards the development of sustainable materials.